2008
DOI: 10.1186/1476-511x-7-27
|View full text |Cite
|
Sign up to set email alerts
|

The prevention of endothelial dysfunction through endothelial cell apoptosis inhibition in a hypercholesterolemic rabbit model: the effect of L-arginine supplementation

Abstract: Background: The impact of L-arginine on atherogenesis and its ability to prevent endothelial dysfunction have been studied extensively during the past years. L-arginine is a substance for nitric oxide synthesis which involves in apoptosis. Hypercholesterolemia promotes endothelial dysfunction, and it is hypothesized that L-arginine prevents endothelial dysfunction through endothelial cells apoptosis inhibition. To test this hypothesis, thirty rabbits were assigned into two groups. The control group received 1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…L-arginine (a NOS substrate) depletion in animal models of atherosclerosis and hypercholesterolemia induces platelet aggregation, cell proliferation, and vascular monocyte accumulation, whereas endothelial-dependent vasoreactivity is improved in hypercholesterolemic rabbits treated with L-arginine, thus attenuating the mechanisms of vascular lesion 26 and inhibiting neointimal proliferation 27 , which can be assessed by means of several endothelial cell markers proposed (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…L-arginine (a NOS substrate) depletion in animal models of atherosclerosis and hypercholesterolemia induces platelet aggregation, cell proliferation, and vascular monocyte accumulation, whereas endothelial-dependent vasoreactivity is improved in hypercholesterolemic rabbits treated with L-arginine, thus attenuating the mechanisms of vascular lesion 26 and inhibiting neointimal proliferation 27 , which can be assessed by means of several endothelial cell markers proposed (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The apoptosis rate of smooth muscle cells in atherosclerotic lesions was shown to be 11±7.8% in miniature pigs on a high-fat diet for 37 weeks (14). Nematbakhsh et al (15) observed an endothelial cell apoptosis rate of 8% in hyperlipidemic rabbits. However, the reason for the significant difference in the apoptosis rate of nerve cells and other cells exposed to hyperlipidemia has not been determined.…”
Section: Neuronal Apoptosis Rate Is Lower Compared To That In Other Cmentioning
confidence: 99%
“…Recently, it was demonstrated that exogenous in vivo NO treatment using nitratethiol, nitrosothiol or nitroglycerine protects SMCs against apoptosis and drives cells to quiescence through up‐regulation of p53 and increased levels of Bcl‐2/Bax (Duran et al ., 2009). Moreover, endothelial cell apoptosis was inhibited in rabbit lesions if the animals received L‐arginine, an essential substance for nitric oxide synthesis (Nematbakhsh et al ., 2008). Interestingly, treatment of plaques in cholesterol‐fed rabbits with the NO donor molsidomine leads to the formation of a large subendothelial macrophage‐free layer solely consisting of SMCs and extracellular matrix (De Meyer et al ., 2003).…”
Section: Pharmacological Stimulation Of Cell Death In Atherosclerosismentioning
confidence: 99%